2008
DOI: 10.1186/1756-3305-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Wolbachia endobacteria in the non-filariid nematodes Angiostrongylus cantonensis and A. costaricensis

Abstract: The majority of filarial nematodes harbour Wolbachia endobacteria, including the major pathogenic species in humans, Onchocerca volvulus, Brugia malayi and Wuchereria bancrofti. These obligate endosymbionts have never been demonstrated unequivocally in any non-filariid nematode. However, a recent report described the detection by PCR of Wolbachia in the metastrongylid nematode, Angiostrongylus cantonensis (rat lungworm), a leading cause of eosinophilic meningitis in humans. To address the intriguing possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Surveys of nonfilarial nematodes have failed to detect Wolbachia outside of this group (Bordenstein et al ., ), although some evidence for divergent Wolbachia ‐like sequences and structurally distinct bacteria has been reported in the plant parasitic Tylenchid nematode, Radopholus similis (Haegeman et al ., ). Reports of PCR amplification of Wolbachia sequence from the metastrongylid nematode Angiostrongylus cantonensis (Tsai et al ., ) have not been reproduced and appear to be because of laboratory contamination (Foster et al ., ). A more in‐depth survey of subfamilies of the Onchocercidae supports the view that Wolbachia arose late in the divergence of filarial nematodes.…”
Section: Symbionts Of Nematodesmentioning
confidence: 97%
See 1 more Smart Citation
“…Surveys of nonfilarial nematodes have failed to detect Wolbachia outside of this group (Bordenstein et al ., ), although some evidence for divergent Wolbachia ‐like sequences and structurally distinct bacteria has been reported in the plant parasitic Tylenchid nematode, Radopholus similis (Haegeman et al ., ). Reports of PCR amplification of Wolbachia sequence from the metastrongylid nematode Angiostrongylus cantonensis (Tsai et al ., ) have not been reproduced and appear to be because of laboratory contamination (Foster et al ., ). A more in‐depth survey of subfamilies of the Onchocercidae supports the view that Wolbachia arose late in the divergence of filarial nematodes.…”
Section: Symbionts Of Nematodesmentioning
confidence: 97%
“…Reductive evolution among allopatric symbionts (of ticks & nematodes) and large genomes for sympatric symbionts present in amoebae Moliner & Raoult (2010) *Adapted from Greub & Raoult (2004). (Foster et al, 2008). A more in-depth survey of subfamilies of the Onchocercidae supports the view that Wolbachia arose late in the divergence of filarial nematodes.…”
Section: Molinermentioning
confidence: 97%
“…The other Wolbachia found in nematodes are much less well-studied. Some onchocercid nematodes carry a Wolbachia that is placed in supergroup F, alongside Wolbachia from termites, fleas and bedbugs (Bordenstein et al 2003 ; Duron and Gavotte, 2007 ; Foster et al 2008 ; Jacob et al 2008 ; Haegeman et al 2009 ; Comandatore et al 2013 ). Initial analyses suggested that the R. similis Wolbachia was distantly related to any other supergroup (Jacob et al 2008 ; Haegeman et al 2009 ), but this result is questionable (Koutsovoulos et al 2014 ).…”
Section: Bacterial Symbiontsmentioning
confidence: 99%
“…The suitability of the extracted S. digitata gDNA for PCR was examined via the attempted amplification of a portion of the S. digitata single copy gene (SDNP) using the following primers: UNF2 (5 -ATT TTC TCG CTG ACC AC-3 ) and UNR (5 -TCA GTA ATT AAT CAA ATT CGG AAG TCT-3 ) (Rodrigo et al, 2014). S. digitata genomic DNA was initially amplified by PCR using primers that were designed for Wolbachia surface protein (WSP) and the 16S rRNA genes of Wolbachia (Foster et al, 2008) and subsequently using primers that were employed for the multilocus sequence typing (MLST) for Wolbachia (Fig. 1).…”
Section: Screening For Wolbachia In S Digitatamentioning
confidence: 99%